1980
DOI: 10.5271/sjweh.2610
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic action of isocyanates used in the production of polyurethanes.

Abstract: The following articles refer to this text: 1982;8(1):0; 1981;7(3):157-240

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…Since 4,4'-methylenedianiline has been demonstrated to be mutagenic after metabolic activation (Darby et al, 1978;Anderson et al, 1980), 4,4'-methylenedianiline's thyroid carcinogenic activity may involve a genetic mechanism of action. There is also a potential for nonDownloaded by [Stockholm University Library] at 20:02 12 August 2015 genetic mechanism of carcinogenesis involving thyroid hormone activity or inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Since 4,4'-methylenedianiline has been demonstrated to be mutagenic after metabolic activation (Darby et al, 1978;Anderson et al, 1980), 4,4'-methylenedianiline's thyroid carcinogenic activity may involve a genetic mechanism of action. There is also a potential for nonDownloaded by [Stockholm University Library] at 20:02 12 August 2015 genetic mechanism of carcinogenesis involving thyroid hormone activity or inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings [33][34][35][36] , especially using Ames test [33][34]36) , need consideration. While many studies found positive Ames tests with MDI and TDI, these used DMSO (dimethylsulfoxid) or other solvents to disperse the diisocyanates into the medium.…”
Section: Mutagenicitymentioning
confidence: 99%
“…We consider it therefore necessary to repeat the basis for our conclusions that "isocyanates must be considered to represent a serious health hazard [p 221]" (2).…”
Section: Authors' Response To Wf Diller's Letter To the Editor -Scandmentioning
confidence: 99%